Two successive cesarean deliveries through separate posterior and anterior hysterotomy due to asymptomatic uterine torsion. A case report - Matthias Boogaerts; Kathleen Wuyts; Henri Joos (Elsevier, 2022)
Uterine torsion during pregnancy is a rare obstetrical complication that can be life-threatening for both mother and child. Although torsion usually presents with acute, non-specific symptoms, it can also occur without any symptoms and pose no immediate health threat. Ultimately, the diagnosis of torsion is often made only during cesarean section.We present a case of a patient who underwent two successive cesarean sections through separate posterior and anterior hysterotomy due to asymptomatic uterine torsion in both cases. During the first cesarean section an incision was inadvertently made in the posterior segment of the uterus. At the second cesarean section the degree of rotation was very different and an anterior hysterotomy was performed. The patient made an uneventful recovery after both deliveries.If access to the lower anterior uterine segment is not safely available due to uterine torsion, a hysterotomy in the lower posterior uterine segment can be performed. The risk of rupture of a posterior hysterotomy scar in future pregnancies is unclear.